Seasonal variation in biopsy‐proven giant cell arteritis in Eastern Denmark from 1990‐2018. Issue 5 (19th November 2020) - Kønig, Elisabeth Bay; Stormly Hansen, Michael; Foldager, Jonathan; Siersma, Volkert; Loft, Annika; Terslev, Lene; Møller Døhn, Uffe; Radmer Jensen, Mads; Wiencke, Anne Katrine; Faber, Carsten; Hamann, Steffen; Heegaard, Steffen
Abstract: Purpose: The purpose of this study was to investigate seasonal variation in cases of biopsy‐proven GCA in eastern Denmark in a 29‐year period. Methods: Pathology records of all temporal artery biopsies in eastern Denmark between 1990 and 2018 were reviewed. For each patient, data were collected which included age, sex, date of birth and biopsy result. Seasonality was evaluated using logistic regression and Poisson regression analysis. Lastly, an explorative pilot study was conducted to investigate a possible association between three weather parameters (average temperature, amount of rain and hours of sunshine) and the biopsy outcome. Results: One thousand three hundred twenty‐three biopsies were included of which 336 fulfilled objective criteria for GCA diagnosis. Mean age at diagnosis was 75.6 years (range 52–94 years). Among the biopsy‐proven cases of GCA, there were 223 women (66.3%, mean age 76.2 years) and 113 men (33.7%, mean age 74.4 years) giving a female to male ratio of 1.97:1. The peak occurrence of GCA was in the 70–79 years age group. Statistical analysis of seasonal variation showed an increased risk of a positive biopsy during summer compared to autumn (p = 0.037). No association between the three weather parameters and the biopsy outcome was found. Conclusion: In this study of biopsy‐proven GCA in a large Danish patient cohort, the occurrence of GCA showed seasonal variation with higher occurrence in the summer months when compared to autumn. Future studies pooling all cases of GCA worldwide are needed to determine seasonality in the occurrence of GCA.